Global agricultural knowledge sharing: the CGIAR libraries consortium - Allmand, M.; Ramos, M.M.; Soeripto, S.W.; Goldberg, E.D. (2003)
Information and communication technologies (ICT) have had an enourmous global impact. They affect not only the areas within organizations that address information processes and services but organizations as a whole. The new technologies facilitate broader access and distribution of information through the internet. The libraries and information services of the 16 centers of the Consultative Group for International Agricultural Research (CGIAR) are joining together to share resources and make the information and knowledge of all Centers accessible to the world through a common internet portal. This paper shows the initiatives of the information managament professionals in the CGIAR to pool their resources and move towards the development of strategies for sharing agricultural knowledge within and beyond the system, It describes the formation a community of practice, the knowledge sharing initiative, the organization of a consortium to share resources and the constraints and challenges to achieving it.